2016
DOI: 10.3346/jkms.2016.31.7.1089
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Growth Charts for Kidney Length in Normal Korean Children: a Prospective Observational Study

Abstract: Kidney length is the most useful parameter for clinical measurement of kidney size, and is useful to distinguish acute kidney injury from chronic kidney disease. In this prospective observational study of 437 normal children aged between 0 and < 13 years, kidney length was measured using sonography. There were good correlations between kidney length and somatic values, including age, weight, height, and body surface area. The rapid growth of height during the first 2 years of life was intimately associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
24
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 21 publications
5
24
2
2
Order By: Relevance
“…In the present study, all the variables, i.e., height, weight, age, and BSA correlated significantly with renal length and volume on univariate regression analysis, as in prior studies ( 3 4 25 ). Of these variables, height and age had the largest R 2 on univariate regression analysis for renal length.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In the present study, all the variables, i.e., height, weight, age, and BSA correlated significantly with renal length and volume on univariate regression analysis, as in prior studies ( 3 4 25 ). Of these variables, height and age had the largest R 2 on univariate regression analysis for renal length.…”
Section: Discussionsupporting
confidence: 81%
“…Second, there is a risk that renal length measured on the coronal plane can be underestimated because the kidney axis is oblique rather than parallel to the coronal plane. Compared to the study reported in 2016 by Oh et al ( 25 ) in Korea, the renal length in the 7-year-old age group to the 11-year-old age group was, on average, shorter by 0.1 cm in this study. In the 6-year-old age group, the difference was approximately 0.7 cm.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The study found that no significant difference found in spleen, left kidney length and ratio in different gender, measurements is more in male than female (Table 3), this results go online with by Eze CU, Agwu KK, Ezeasor DN, Agwuna KK 2014, A Otiv, K Mehta, U Ali 2012, Ravi kumar Nalli, et al, and Oh M-S, et al, whom stated that there was no significant difference between the renal lengths of male and female. [10][11][12][13] The study found that there was significant correlation between age, height, weight, BMI with splenic length, AP, width (p<0.01), this results go online with These results go online with Bhavna Dhingra, et al 2010 whom state that there was significant correlation between spleen size age, weight and height. 14 The study found that there was significant correlation between age, height, weight, BMI of participant and left kidney length, width and AP (p<0.01), these results agree Ravi kumar Nalli, et al 2012-2013 whom state there was significant correlation between age, height and weight with kidneys length and volume.…”
Section: Discussionmentioning
confidence: 87%
“…5,10 For comparing left kidney measurements, with age for five age group the study reveals that the mean length of left kidney increased steadily with age from (5.92±0.79 cm) at group one to (7.93±0.92 cm) at group, spleen length in group one 6.12±0.90 cm and in group five 8.33±0.75 cm, the left kidney length and spleen length increased with increasing age and there are strong significance correlation with (p<0.01) table 2, the present study agree also with study done by (A Otiv, K Mehta, U Ali, 2012),(Ravikumar Nalli, 2016) whose found that there was significant correlation of kidney length with age. 11,12 The study found that spleen to left kidney length has no significant difference in difference age group in group one 1.03±0.07 and in group five 1.05±0.05 ( p>0.05)…”
Section: Discussionmentioning
confidence: 89%